Assessment and Optimization of Boiler Energy Efficiency at Universiti Tun Hussein Onn Malaysia - Samsudin, Ahmad Samir; Razali, Mohd Azahari; Nur Syafiqah Adha Narrudin; Nur Erma Nardiah Nazami; Masataro Suzuki (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This technical report presents a comprehensive energy audit of the boiler systems at Universiti Tun Hussein Onn Malaysia, evaluating its boiler efficiency and identifying energy conservation measures by using sophisticated instrumentation such as the ST9450 thermal imaging camera, Fluke 59 Max infrared thermometer, and Meatrol ME435 Multi-Functional Power Quality Analyzer Data Logger Power Meter. This audit collected precise data on power consumption, surface temperatures, and heat leakages. This audit involved a detailed walk-through of the boiler plant room and steam supply system, followed by rigorous measurements and data analysis. Key parameters measured included flue gas temperature and steam supply pressures. Thermal imaging revealed significant heat leakages, suggesting areas for improved insulation. The data highlighted inefficiencies and potential energy savings. The findings contribute to lowering operational costs, reducing the university's environmental footprint, and enhancing educational opportunities for students.